Analysis of patient-reported outcomes from the LUME-Lung 1 trial: A randomised, double-blind, placebo-controlled, Phase III study of second-line nintedanib in patients with advanced non-small cell lung cancer. Issue 3 (February 2015) - Novello, Silvia; Kaiser, Rolf; Mellemgaard, Anders; Douillard, Jean-Yves; Orlov, Sergey; Krzakowski, Maciej; von Pawel, Joachim; Gottfried, Maya; Bondarenko, Igor; Liao, Meilin; Barrueco, José; Gaschler-Markefski, Birgit; et al.
Abstract Introduction The LUME-Lung 1 trial (NCT00805194; Study 1199.13) demonstrated a significant overall survival (OS) advantage for nintedanib plus docetaxel compared with placebo plus docetaxel as second-line therapy for patients with advanced non-small cell lung cancer (NSCLC) and adenocarcinoma histology. Patient-reported outcomes (PROs) for symptoms and health-related quality of life (QoL) are reported here. Methods PROs were assessed at screening, on Day 1 of each 21-day treatment cycle, at the end of active treatment, and at the first follow-up visit. PRO instruments were the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 and Lung Cancer-13 supplement, and the EuroQol disease-generic questionnaire (EQ-5D and EQ-VAS). Analyses of PRO items for lung cancer-specific symptoms of cough, dyspnoea and pain were prespecified. Results Rates of questionnaire completion were high. There was no significant difference in time to deterioration of global health status/QoL, or symptoms of cough, dyspnoea or pain, between the treatment groups for both the overall study population and the adenocarcinoma population. Time to deterioration of some gastrointestinal events was shorter with nintedanib versus placebo. Longitudinal analysis for the adenocarcinoma population showed comparable changes between the groups in symptom scores over time, with numerical differences in favour of nintedanib for cough and pain scales, and significant reductions in some pain items with nintedanib versus placebo. There was no statistically significant difference in EQ-5D or EQ-VAS between the groups. Conclusion The significant OS benefit observed with the addition of nintedanib to docetaxel therapy was achieved with no detrimental effect on patient self-reported QoL.